2010
DOI: 10.1007/s12031-010-9403-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Serum Tau Protein Predict the Outcome of Patients with Ischemic Stroke?

Abstract: The prediction of outcome after ischemic stroke (IS) is currently based on indirect data from clinical and radiological evaluation. We evaluated the usefulness of serum Tau protein as possible prognostic markers for IS. Fifty-six patients with computed tomography-confirmed IS were enrolled. Blood samples were obtained on days 1, 3, 5, and 10 after stroke onset. Tau and S100BB serum levels were measured by commercially available enzyme-linked immunosorbent assay. Neurological deficits were quantified by the Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 17 publications
7
33
0
Order By: Relevance
“…A study of experimental brain injury in rats found that serum tau levels increased by more than fourfold in the hour following the insult [Liliang et al, ], indicating that the tau protein from the brain is readily excreted into the peripheral blood shortly after it is produced. Therefore, the elevated CSF tau levels that are observed in subjects with AD should result in elevated plasma tau levels that are similar to the levels that have been reported in the other aforementioned clinical studies [Bielewicz et al, ; Liliang et al, ; Mörtberg et al, ; Noguchi‐Shinohara et al, ]. Plasma tau can therefore be considered to be a window that reveals brain structure in terms of both total brain volume and the gray matter density of the hippocampus.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A study of experimental brain injury in rats found that serum tau levels increased by more than fourfold in the hour following the insult [Liliang et al, ], indicating that the tau protein from the brain is readily excreted into the peripheral blood shortly after it is produced. Therefore, the elevated CSF tau levels that are observed in subjects with AD should result in elevated plasma tau levels that are similar to the levels that have been reported in the other aforementioned clinical studies [Bielewicz et al, ; Liliang et al, ; Mörtberg et al, ; Noguchi‐Shinohara et al, ]. Plasma tau can therefore be considered to be a window that reveals brain structure in terms of both total brain volume and the gray matter density of the hippocampus.…”
Section: Discussionsupporting
confidence: 70%
“…Although the results of this previous study may have been limited by the relatively low sensitivity of the ELISA technology that it used, a more recent study that employed an ELISA technique with greater sensitivity to detect tau levels reported reduced plasma tau levels in patients with AD [Sparks et al, ]. Other studies that have used these more sensitive ELISA approaches have reported that plasma tau levels were increased in the late phase of comatose patients who had experienced cardiac arrest [Mörtberg et al, ] and in patients with Creutzfeldt‐Jakob disease, acute stroke, and traumatic brain injury [Bielewicz et al, ; Liliang et al, ; Noguchi‐Shinohara et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, this is less of a problem when investigating plasma tau levels as tau is more CNS-specific, and clearly more research is needed regarding tau as a biomarker for AD in DS. However, tau is not specific to AD pathology, and blood tau levels have been shown to be increased in other CNS pathologies, such as traumatic brain injury and cerebral infarction (Bielewicz, Kurzepa, Czekajska-Chehab, Stelmasiak, & Bartosik-Psujek, 2010;Liliang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, plasma tau levels are elevated in a series of pathologies, such as ischemic stroke [96], Creutzfeldt-Jacobs disease [97], and traumatic brain injury [98]. For hyperphosphorylated tau, there are no studies that show clear any relevance of this marker in serum/ plasma [4,12].…”
Section: A Critical Evaluation Of Ongoing Biomarker Approachesmentioning
confidence: 99%